Lady Dicks and Lesbian Brothers Staging the Unimaginable at the WOW Cafe Theater - Davy, Kate (University of Michigan Press, 2010)
Out of a small, hand-to-mouth women's theater collective called the WOW Café located on the lower east side of Manhattan there emerged some of the most important theater troupes and performance artists of the 1980s and 1990s. Appearing on the cultural scene at a critical turning point in both the women's movement and feminist theory, WOW put a witty, hilarious, gender-bending, and erotically charged aesthetic on stage for women in general and lesbians in particular. Featured performers included the Split Britches Company, the Five Lesbian Brothers, Carmelita Tropicana, Holly Hughes, Lisa Kron, Deb Margolin, Reno, Peggy Shaw, and Lois Weaver. For three decades the WOW Café Theatre has nurtured fledgling women writers, designers, and performers who continue to create important performance work. Lady Dicks and Lesbian Brothers offers the first critical history of the WOW Café, based on dozens of interviews with WOW performers and other participants, newspaper reviews of the earliest productions, and unpublished photographs, and suggests why the collective has had such amazing longevity and an enduring legacy.